Control of Reactive Power and Connection Voltage in Grid Connected Wind Turbine - Karimi, Hamed; Tarassodi, Pouya; Siadatan, Alireza; Sepehrinour, Maryam (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2024)
Due to the development and progress of countries, with the passage of time, our need for electrical energy also increases, but electricity production relies on fossil energy sources, which are both running out and cause the production of greenhouse gases, but on the other hand, because energy is cheap. Wind this renewable energy has been developed rapidly on a global scale. However, due to the fact that in wind power plants, wind speed will not always be constant and it is changing, this problem disturbs the balance of the power system and causes the voltage to always change, for this reason, the grids in which there is a wind turbine are different from each other. grids are different and many researches and studies have been done to solve this problem, and due to its many advantages, the Doubly Fed Induction Generator (DFIG) is considered to compensate for these problems, by using it, we will not need to compensate for additional reactive devices We had and can control the speed, active and reactive power.